Pengaruh Storytelling Marketing dan Citra Destinasi terhadap Minat Berkunjung Kembali dengan Tourist Satisfaction sebagai Variabel Intervening pada Pengunjung Tanaria Park - Fadilah, Nur Lailatul; Huda, Miftahul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The tourism industry plays an important role in the economy, including reducing unemployment and increasing productivity. This growth is triggered by tourist visits, so destination managers need to attract and ensure tourists return by offering interesting experiences, a strong destination image and adequate satisfaction. This research aims to determine the influence of Storytelling Marketing, Destination Image on Intention to Revisit with Tourist Satisfaction as an Intervening Variable among Tanaria Park tourist visitors. The type of research used in this research is explanatory research with a quantitative approach. The sampling technique was carried out using the Accidental Sampling technique. The number of samples in this study was 96 respondents. Data collection was carried out by distributing questionnaires directly to Tanaria Park tourist visitors who were the object of research. The data obtained in this research was analyzed using Path Analysis with a calculation analysis tool using SPSS 22. The results of this research show that the Storytelling Marketing variable has a positive and significant effect on Tourist Satisfaction, Destination Image has a positive and significant effect on Tourist Satisfaction, Storytelling Marketing has a positive and significant effect on Interest in Returning, Destination Image has a positive and significant effect on Interest in Returning, Tourist Satisfaction has a positive and significant effect on Intention to Return to Visit.